2019
DOI: 10.5194/nhess-19-2619-2019
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami hazard and risk assessment for multiple buildings by considering the spatial correlation of wave height using copulas

Abstract: Abstract. It is necessary to evaluate aggregate damage probability to multiple buildings when performing probabilistic risk assessment for the buildings. The purpose of this study is to demonstrate a method of tsunami hazard and risk assessment for two buildings far away from each other, using copulas of tsunami hazards that consider the nonlinear spatial correlation of tsunami wave heights. First, we simulated the wave heights considering uncertainty by varying the slip amount and fault depths. The frequency … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Risk assessment is not necessarily limited to quantifying the direct and indirect impact on exposed populations and infrastructures. The evaluation of safety and reliability of physical systems is of interest too and for this, fragility functions ("Gaps in Physical Vulnerability" section) can be integrated with hazard to obtain the frequency of exceeding a given damage level (see Figure 1, e.g., Park et al, 2019;Fukutani et al, 2019). The risk metrics provide valuable data also for the assessment of quantitative resilience (also denoted as engineering resilience), which aims to estimate the resilience of a network, an infrastructure, or even an urban ecosystem to a specific natural hazard (see Mebarki et al, 2016 for industrial plants, Akiyama et al, 2020 for bridges).…”
Section: Gaps In Risk and Resilience Metricsmentioning
confidence: 99%
“…Risk assessment is not necessarily limited to quantifying the direct and indirect impact on exposed populations and infrastructures. The evaluation of safety and reliability of physical systems is of interest too and for this, fragility functions ("Gaps in Physical Vulnerability" section) can be integrated with hazard to obtain the frequency of exceeding a given damage level (see Figure 1, e.g., Park et al, 2019;Fukutani et al, 2019). The risk metrics provide valuable data also for the assessment of quantitative resilience (also denoted as engineering resilience), which aims to estimate the resilience of a network, an infrastructure, or even an urban ecosystem to a specific natural hazard (see Mebarki et al, 2016 for industrial plants, Akiyama et al, 2020 for bridges).…”
Section: Gaps In Risk and Resilience Metricsmentioning
confidence: 99%
“…This approach is also widely accepted, and several studies have been reported. Among these is a study on making real-time predictions using source information and precomputed tsunami waveform and inundation databases (Gusman et al, 2014), another uses a combination of precomputed tsunami databases and the neural networks (Fauzi and Mizutani, 2019;Liu et al, 2021), and another features the surrogate modeling of numerical simulation results (e.g., Fukutani et al, 2019;Kotani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a surrogate-modeling-based prediction method is employed in this study. Surrogate modeling has been widely accepted for uncertainty quantification and probabilistic risk assessment, such as studies using response surface (e.g., Fukutani et al, 2019;Kotani et al, 2020), Gaussian process (e.g., Sarri et al, 2012;Salmanidou et al, 2017Salmanidou et al, , 2021, polynomial chaos expansion (e.g., Denamiel et al, 2019;Giraldi et al, 2017;Sraj et al, 2017) and multifidelity sparse grids (e.g., de Baar and Roberts, 2017). These works demonstrate the potential of the surrogate-modeling-based approach, while the surrogate model considering spatiotemporal variation has not been well studied.…”
Section: Introductionmentioning
confidence: 99%